Intrinsic heart rate recovery after dynamic exercise is improved with an increased omega-3 index in healthy males - Michael J. Macartney; Lachlan Hingley; Marc A. Brown; Gregory E. Peoples; Peter L. McLennan (2014)
Dietary fish consumption contributes to a reduced risk of cardiac mortality. In the present study, the effect of low-dose fish oil (FO) supplementation on heart rate (HR) response to intense exercise and recovery was investigated in physically fit males. The subjects ( n 26) were supplemented (double-blind, parallel design) with (2 × 1 g/d) soya bean oil (control) or tuna FO providing the long-chain n -3 PUFA DHA (560 mg) and EPA (140 mg). Erythrocyte omega-3 index (%EPA+DHA), HR, HR variability and HR recovery were analysed during rest, intense exercise and recovery at baseline and after 8 weeks of supplementation. The mean erythrocyte omega-3 index, which did not differ between the groups at baseline (control 4·2 ( sem 0·2), n 13; FO 4·7 ( sem 0·2), n 13), remained unchanged in the control group (3·9 ( sem 0·2)), but increased in the FO group (6·3 ( sem 0·3); P < 0·01). The mean HR during supine resting conditions (control 56 ( sem 10); FO 59 ( sem 9)) was not affected by FO supplementation. Poincaré analysis of HR variability at rest exhibited a decreasing trend in parasympathetic activity in the FO group (SD1 (standard deviation of points perpendicular to the axis of line of identity)/SD2 (standard deviation of points along the axis of line of identity): control 0·02 ( sem 0·01); FO − 0·05 ( sem 0·02); P = 0·18). Peak HR was not affected by supplementation. However, during submaximal exercise over 5 min, fewer total heart beats were recorded in the FO group ( − 22 ( sem 6) ( = − 4·5 beats/min)), but not in the control group (+1 ( sem 4)) ( P < 0·05). Supine HR recovery (half-time) after cycling was significantly faster after FO supplementation (control − 0·4 ( sem 1·2) s; FO − 8·0 ( sem 1·7) s; P < 0·05). A low intake of FO increased the omega-3 index and reduced the mean exercise HR and improved HR recovery without compromising the peak HR. A direct influence of DHA via reductions in the cardiac intrinsic beat rate was balanced by a reciprocal decrease in vagal tone.